Clinical characteristics and risk factors of severe infections in hospitalized adult patients with primary nephrotic syndrome. (December 2017) - Li, Jie; Zhang, Qiankun; Su, Bofeng
Objective: Infection is a common condition in patients with nephrotic syndrome. The objective of the present study is to investigate the clinical characteristics and risk factors of infections in adult patients with primary nephrotic syndrome (PNS). Methods: Medical charts of 138 consecutive patients with PNS and infections who were admitted to hospital from April 2013 to April 2016 were systematically reviewed. Results: Patients were divided into three groups according to the degree of infections: mild infection group (n = 45), moderate infection group (n = 60), and severe infection group (n = 33). In the severe infection group, most patients (96.9%) had pulmonary infections with opportunistic pathogens. There were significant differences in cumulative prednisone dose, immunosuppressor use, and CD4+ T cell count among the three groups. A lower CD4+ T cell count (<300 cells/mm 3 ) (odds ratio = 4.25 [95% confidence interval 1.680–10.98]) and higher cumulative dose of prednisone (odds ratio = 1.38 [95% confidence interval 1.05–3.26]) were risk factors for severe infections in adult patients with PNS. Conclusions: CD4+ T cell count (<300 cells/mm 3 ) and a higher cumulative dose of prednisone are important risk factors for severe infections in adult patients with PNS.